Problems of Assessment of Social and Economic Efficiency of Taxation in the RA - Panosyan, Meri (Bulletin of Yerevan University G: Economics, 2022)
The article examines the tax/GDP ratio characterizing the efficiency of taxation, the percentage ratio of direct and indirect taxes in the RA, and the influence of the volume of shadow circulation from the point of view of the efficiency of taxation. As a result of the analysis, it became clear that although the efficiency of VAT flow management in Armenia is high, the diversification of tax levy and the inflow of differentiated tax revenues are low, the tax burden is mainly aimed at consumption, which, affecting the level of purchasing power, also affects on the elasticity of demand caused by the price of the product, along with the high tax burden, the quality of life of the population is low, and there is also a causal relationship between the behavior of taxpayers and the volume of shadow turnover. The main reason for these problems is the social and economic imbalance of the tax potential of the economy. Estimating the level of taxation efficiency using the above mentioned methods is quite complicated and ambiguous, because the calculation of these indicators requires a justified combination and consistent protection of the interests of all social groups, justification of the fairness of the uneven distribution of the tax burden in branch spheres, and the formation of law-abiding behavior of taxpayers by reducing the volume of shadow circulation. Nevertheless, the level of taxation efficiency will increase if the state can balance the demand for its financial means and the solvency of taxpayers, taking into account their standard of living and social belonging․
Keywords: coefficient of taxing efficiency; gross domestic product; tax burden; principle of justice; direct taxes; indirect taxes; shadow economy; social inequality